An Error Analysis on TFL Learners’ Writings - ÇERÇİ, Arif (Gaziantep University, 2018)
The main purpose of the present study is to identify and represent TFL learners’ writing errors through error analysis. All the learners started learning Turkish as foreign language with A1 (beginner) level and completed the process by taking C1 (advanced) certificate in TÖMER at Gaziantep University. The data of the present study were collected from 14 students’ writings in proficiency exams for each level. The data were grouped as grammatical, syntactic, spelling, punctuation, and word choice errors. The ratio and categorical distributions of identified errors were analyzed through error analysis. The data were analyzed through statistical procedures in an effort to determine whether error types differ according to the levels of the students. The errors in this study are limited to the linguistic and intralingual developmental errors